Effect of Oral Medroxyprogesterone Acetate and Nutritional Supplementation during Late Gestation on Birth Weight in Nellore Sheep - Dabbir, Rao Balakrishna; Bhat, Shridhar Narayan; Tikare, Vinay; Rajavolu, Srinivasa Reddy; Prasad, Prajwal Kadirampalli Reddy (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted to evaluate the effect of oral medroxy progesterone acetate and a liquid nutritional supplement on birth weight and early growth performance in Nellore ewes and their lambs under extensive rearing conditions. A total of 120 second-lambed Nellore ewes in mid to late gestation were randomly allotted into four experimental groups (n=30 each). Group I served as Control, Group II as medroxy progesterone (10 mg tab daily for 5 days), Group III liquid nutritional supplement (5 mL tonic daily for 7 days) and Group IV with combination of medroxy progesterone acetate and liquid nutritional tonic, administered orally during late gestation as above. Mean birth weights of lambs in Group II and Group III were 3.91 ± 0.41, 3.58 ± 0.31 kg against 2.96 ± 0.15 kg in the control group (p
Keywords: Birth weight; Liquid nutritional supplement; Medroxy progesterone acetate; Nellore ewes